PENDAMPINGAN GURU YAYASAN AL-FATIMAH DALAM PENGUATAN KARAKTER PROFIL PALAJAR PANCASILA DAN RAHMATAN LIL ‘ALAMIN MELALUI IMPLEMENTASI KONSEP PENDIDIKAN LUKMAN AL-HAKIM - Ulva Badi' Rohmawati; Hamidatun Nihayah (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2025)
The purpose of this activity is to equip teachers with understanding and skills in instilling the character of Pancasila and rahmatan lil alamin student profiles through the implementation of the Lukman Al-Hakim Education concept. The method used in community service is Advocacy, which is used for activities in the form of mentoring. The strategy used in developing the community is Asset Based Community Development (ABCD). The results of community service are an increase in the knowledge and understanding of Al-Fatimah teachers about the Lukman Al-Hakim Education concept, the implementation of the Lukman Al-Hakim Education concept and the correlation between the Lukman Al-Hakim Education concept with P5 and PPRA. The conclusion of this activity is to help increase the acceleration of P5 and PPRA for Islamic boarding school-based educational institutions, broad and deep knowledge, understanding and skills are needed about various concepts of education in Islam.